Several Compounds Isolated from Stem Bark of Kedoya (Dysoxylum gaudichaudianum (A. Juss.) Miq.) (Meliaceae) - Tukiran Tukiran (Jurnal ILMU DASAR, 2009)
Several compounds, p-hydroxyacetophenone, b-sitosterol and stigmasterol had been isolated from hexane and chloroform extracts of stem bark of kedoya (Dysoxylum gaudichaudianum (A. Juss.) Miq.) (Meliaceae) respectively. These structures had been established based on spectroscopic data (IR and NMR) and by comparison with spectroscopic data of related compounds that had been reported.